River cruise holiday packages: A network analysis combined with a geographic information system framework. (January 2021) - Guedes, Alexandre; Rebelo, João
Abstract: This research analyzes the physical network of river cruise holiday packages as a relational system. A comprehensive network analysis is undertaken based on data from the Douro River (Portugal). Adjacency matrices are built to derive network centrality, constraint, and modularity metrics, further integrated into a Geographic Information System. Centrality and constraint measures are regressed on river-cruise holiday packages' attraction and logistical factors. Results reveal a major impact of logistical attributes rather than attraction on most centrality and constraint metrics. River cruising's destination network proves to be a multimodal transit network structure in a hub-and-spoke network framework, exhibiting several modules linked by connector hubs, which is consistent with a power-law distribution common to real-world networks. The results confirm river cruising's complex physical network of destinations, geographically diffused, which raises systemic and scale concerns that call for an integrated approach that articulates destination planning comprehensively. Graphical abstract: Unlabelled Image Highlights: River cruise holiday packages are based on a multi-destination network pattern. Docking and transport facilities are the main determinants of centrality. River cruise holiday packages exhibit a hierarchical network with a diffused low degree nodality. River cruising's destination management requires an integrated planning approach.